2016
DOI: 10.1371/journal.pone.0166007
|View full text |Cite
|
Sign up to set email alerts
|

Interval of Uncertainty: An Alternative Approach for the Determination of Decision Thresholds, with an Illustrative Application for the Prediction of Prostate Cancer

Abstract: Often, for medical decisions based on test scores, a single decision threshold is determined and the test results are dichotomized into positive and negative diagnoses. It is therefore important to identify the decision threshold with the least number of misclassifications. The proposed method uses trichotomization: it defines an Uncertain Interval around the point of intersection between the two distributions of individuals with and without the targeted disease. In this Uncertain Interval the diagnoses are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Thus, a novel trichotomization method was used also to provide two threshold levels that define an interval of uncertainty around Youden index. Around Youden index the step width variability values are inter-mixed and have a near equal probability of indicating 'reference' or 'excessive' providing little or no information whether an individual is a younger or older adult [37]. The cutoff points of the uncertain interval method were chosen at specificity (Sp) = sensitivity (Se) = 0.50.…”
Section: Identification Of the Optimal Threshold Levels Of Step Widthmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a novel trichotomization method was used also to provide two threshold levels that define an interval of uncertainty around Youden index. Around Youden index the step width variability values are inter-mixed and have a near equal probability of indicating 'reference' or 'excessive' providing little or no information whether an individual is a younger or older adult [37]. The cutoff points of the uncertain interval method were chosen at specificity (Sp) = sensitivity (Se) = 0.50.…”
Section: Identification Of the Optimal Threshold Levels Of Step Widthmentioning
confidence: 99%
“…The positive predictive value (probability to belong to the older adults' groups when step width variability is excessive) was PPV di = 0.71, and the negative predictive value (probability to belong to the younger adults' groups when step width variability is healthy) was NPV di = 1.00. Using the approach of Landsheer, [37] the optimal reference range was separated from the excessive step width variability by an uncertainty interval. The lower and upper threshold levels of the uncertainty interval were Lo = 1.97 cm and Hi = 2.50 cm, respectively.…”
Section: Discrimination Of Step Width Variability For Predicting Age mentioning
confidence: 99%
“…Such inconclusive or uncertain results are an inherent part of the use of diagnostic tests, bio-markers and diagnostic procedures in general. These results have caught the attention of several researchers and are called diagnostically insufficient, inconclusive or grey [ 1 , 2 ], intermediate [ 3 ], uncertain [ 4 , 5 ], equivocal, indeterminate or uninterpretable [ 6 ] or non-evaluable [ 7 ]. Dichotomization of test results, where only decisions for or against the presence of the targeted condition are used, provides no information about these inconclusive test results [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the availability of open-source software as an R package 20 , 26 may be an attractive feature for test developers. Simulation results 21 , 22 have shown that a range around the dichotomous optimal threshold identifies the most error prone test scores more efficiently than alternative methods for trichotomization.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This range of test scores is typically found around the point of intersection of the 2 distributions of patients with and without the targeted impairment. 20 – 22 The point of intersection is equal to the Youden threshold. 23 Standardized predictive values 24 , 25 are most suitable for the determination of uncertain test scores.…”
Section: Methodsmentioning
confidence: 99%